Concluding remarks: What's in a name? "Negritos" in the context of the human prehistory of South East Asia - Ulijaszek, S (Wayne State University Press, 2013)
The "negrito" hypothesis posits that various indigenous groups throughout Island and Mainland Southeast Asia have a shared phenotype due to common descent from a putative ancestral population, representing a preagricultural substrate of humanity in the region. This has been examined and tested many times in the past, with no clear resolution. With many new resources to hand, the articles in this volume reexamine this hypothesis in a range of different ways. The evidence presented in this double issue of Human Biology speaks more against the category of "negrito" than for it. While populations with the negrito phenotype form a small proportion of all contemporary populations in this region, they have remained a persistent presence. And without a fascination about their origins, there would not be such a depth of knowledge about the human biology of this region more broadly as there is now.